2011
DOI: 10.1002/bimj.201000239
|View full text |Cite
|
Sign up to set email alerts
|

Graphical approaches for multiple comparison procedures using weighted Bonferroni, Simes, or parametric tests

Abstract: The confirmatory analysis of pre-specified multiple hypotheses has become common in pivotal clinical trials. In the recent past multiple test procedures have been developed that reflect the relative importance of different study objectives, such as fixed sequence, fallback, and gatekeeping procedures. In addition, graphical approaches have been proposed that facilitate the visualization and communication of Bonferroni-based closed test procedures for common multiple test problems, such as comparing several tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
168
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(168 citation statements)
references
References 49 publications
0
168
0
Order By: Relevance
“…For m ≥ 3, the monotonicity condition (Bretz et al 2011) does not hold for positive correlations, although it holds for the cases of independent or negative correlations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For m ≥ 3, the monotonicity condition (Bretz et al 2011) does not hold for positive correlations, although it holds for the cases of independent or negative correlations.…”
Section: Discussionmentioning
confidence: 99%
“…In situations where the correlations between endpoints are known for some but not for all, Bretz et al (2011) provided a solution, which requires using a submatrix of those fully known correlations for solving Equation (3). It can be shown that their solution preserves consonancy in a consonant parametric procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10] Evaluation of safety along with efficacy in superiority trials has been around for a long time, and solid methodologies have been developed for simultaneous comparisons and multiple endpoint testing. [11][12][13][14][15][16][17][18] Adapting these to NI trials, several approaches for multiple comparison procedures allowing simultaneous testing of noninferiority and superiority of the multiple endpoints in NI trials are available. These include a mixture of graphical approaches, alpha allocation, and hierarchical gatekeeping, eg, Bretz et al 12,13 Bauer et al, 11 Bristol, 18 Nishikawa et al 17 and Guilbaud.…”
mentioning
confidence: 99%